Synthesis of Imidazo[1,2-b]pyridazine Comprised Piperazine, Morpholine Derivatives as Potent Antimycobacterial Agents with In Vivo Locomotor Activity - Paidi, K.R.; Tatipamula, V.B.; Kolli, M.K.; Annam, S.S.P.; Pedakotla, V.R. (Anti-Infective Agents, 2017)
Background: Heterocyclic compounds have attracted much attention to synthetic and medicinal chemists because of their biological activities especially for tuberculosis (TB).Moreover, fatal forms of TB (including tuberculous meningitis) have led to search for new structural anti-TB agents. So, we have built a scaffold using imidazo[1,2-b]pyridazine, piperazine and morpholine moieties, which are widely used in the inhibition of resistant strains of various organisms. Objective: The aim was to synthesise 6-morpholino-3-(piperazine-1-yl)imidazo[1,2-b]pyridazine containing amide and sulphonamide derivatives and evaluate their antimycobacterial and locomotor activities. Methods: The novel imidazo[1,2-b]pyridazine, piperazine and morpholine scaffolds have been synthesized in seven steps. All the synthesized compounds (8a-j) were screened for in vitro antimycobacterial activity against M.tb H37Rv strains using the MABA, in vivo locomotor activity by using photoactometer and rotarod apparatus. Results: All the synthesized imidazo[1,2-b]pyridazine analogues were characterized by 1H NMR, 13C NMR and ESI-MS. The compounds 8h and 8j exhibited potent in vitro anti-TB activity at 1.6 μg/mL concentration. Based on the structural and in vitro studies, we had related SAR of 8a-j. Overall, the amide derivatives showed better antitubercular activity than sulphonamide derivatives, which might be due to easy hydrogen bond formation. Moreover, all the derivatives showed significant CNS depressant action lacking neurotoxicity that indicates that the compounds 8a-j have strong lipophilic nature. Conclusion: The presence of novel structure, lipophilicity and non-toxic nature provide impetus for compounds 8a-j in the diagnosis of TB and tuberculous meningitis along with first line anti-TB drugs.
Keywords: Imidazo[1